Modeling of the Near-Earth Low-Energy Antiproton Fluxes - U. B. Jayanthi; A. A. Gusev (Advances in Astronomy)
The local interstellar antiproton spectrum is simulated taking into account antineutron decay, (He,p) interaction, secondary and tertiary antiproton production, and the solar modulation in the “force field” approximation. Inclusive invariant cross-sections were obtained through a Monte Carlo procedure using the Multistage Dynamical Model code simulating various processes of the particle production. The results of the simulations provided flux values of 4⋅10−3 to 10−2 and 10−2 to 1.7⋅10−2 antiprotons/(𝑚2 s sr GeV) at energies of 0.2 and 1 GeV, respectively, for the solar maximum and minimum epochs. Simulated flux of the trapped antiprotons in the inner magnetosphere due to galactic cosmic ray (GCR) interactions with the atmospheric constituents exceeds the galactic antiproton flux up to several orders. These simulation results considering the assumptions with the attendant limitations are in comprehensive agreement with the experimental data including the PAMELA ones.